Empreendedorismo no campo da economia criativa: um estudo sobre a feira de artesanato da Beira Mar - Silva, Felipe Maia Balbueno da (2014)
This research has as main objective to verify characterized as entrepreneurial activity at Beira Mar craft fair. To this end, the following specific objectives were: 1) Identify the profile of the exhibitors at the Craft Fair of Beira Mar; 2) Identify the types of crafts sold at most craft fair Beira Mar; 3) Identify the key techniques of the crafts sold at the Fair craft Beira Mar; 4) Identify key motivators, facilitators and barriers to entrepreneurial activity of the exhibitors at the fair; 5) Assess the entrepreneurial potential of the craft fair exhibitors Beira Mar. In order to achieve these objectives, we used as instruments of data collection the Carland Entrepreneurship Index - CEI developed by Carland, Carland and Hoy (1992) and own instrument developed by the author based on the theoretical framework discussed. The research is a descriptive-analytical quantitative, survey, and its population composed of artisans who work in the Crafts fair Beira Mar. This population was chosen for convenience. Because the "feirinha da Beira Mar" is a traditional point and sample sale Ceará craft a considerable number of artisans who gather there daily marketing its products. This population consists of about 645 people, with the study sample comprised 68 people. It was verified that the Ceará artisans are mostly classified as entrepreneurs. The majority being female artisans are generally between 36 and 50 years of age possessing average level of education completed. Fairs are the main form of artisans to market their merchandise that fits mostly in the type of "wire and fabric" using the technique of production of embroidery and lace. Main facilitators for the activity was cited tourism and low cost to operate the branch, whereas barriers have been identified as intense competition, the uncertainty of earnings, legal and supervisory issues and the lack of infrastructure for the branch. The need for jobs and income, high-demand and personal satisfaction were the main factors cited as motivators to engage in the business of craft.